Caos, Emergentismo y Estados Mentales: Un Análisis de la Frontera entre la Física y la Mente - Aboites, Vicente (Acta Universitaria, 2009)
From an internalist viewpoint for mental states, it is proposed that any dynamical system with coexisting chaotic attractors has an emergent property. This provides a non reductive explanation of mental states and their high sensitivity to noise and initial conditions. If metaphysical terms result from the mental states and these are emergent properties of dynamical systems with coexisting attractors, such as the brain, it is suggested that this may provide a physical explanation of metaphysical concepts. Essentially the question we would like to analyze is the following: Could brain mental states be grounded in chaotic multistable states of the brain. It is conjectured that is this is the case, mental states could be identified with specific physical states of our brain. The purpose of this work is to explain the previous ideas from the actual scientific perspective of non linear dynamics, the theory of chaos and its relation to emergentism.